Prediksi Mahasiswa Berpotensi Berhenti Kuliah Secara Sepihak Menggunakan Data Mining Algoritma C4.5 - Sudarsono, Bernadus Gunawan; Bani, Alexius Ulan (J-SAKTI (Jurnal Sains Komputer dan Informatika), 2020)
Students are a call to a student who has sat in college; there are many reasons why students decide to stop taking one-sidedly lectures which result in many losses that will be experienced by the campus, starting from reduced campus quantities and campus quality, adding to the accumulation of unclear student data and will cause and slow down the campus reporting performance. Hence, it is necessary to predict students who have the potential to stop studying unilaterally by looking at several criteria and digging up information on potential student data by applying data mining science and approaching one of the classification approach algorithms, namely the C4.5 algorithm; the results obtained from the study can see the predictive rule of students who have the potential to unilaterally quit college.